Preparation and Reactions of CF3‐Containing Phthalides. Issue 48 (25th November 2018) - Mitobe, Kana; Terashima, Kyu; Kawasaki‐Takasuka, Tomoko; Agou, Tomohiro; Kubota, Toshio; Yamazaki, Takashi
Abstract : We have demonstrated that reactions of aromatic 1, 2‐diesters and the Ruppert–Prakash reagent (TMSCF3 ) afforded hitherto unknown phthalides 1 with both trifluoromethyl (CF3 ) and alkoxy groups at the 3 position, and their unique transformation was also investigated in detail to attain construction of a variety of very rare types of compounds, such as 1, 3‐dihydroisobenzofurans 8 as well as indanones 9 with a CF3 moiety, whose behavior was completely different from the structurally similar compound 2a . Abstract : A variety of transformation of unprecedented phthalides readily formed by the reaction of TMSCF3 and aromatic 1, 2‐diesters resulted in obtaining different types of CF3 ‐containing compounds, which were almost inaccessible by previously developed methods.